An Investigation into the Use of a Movement Assessment Protocol for Under-14 Rugby League Players in a Talent Development Environment. Issue 4 (August 2015) - Morley, David; Pyke, Daniel; Till, Kevin
This study investigated the use of a movement assessment protocol for under-14 rugby league players by evaluating the relationships between chronological age, maturation, and anthropometry, and fitness and qualitative movement assessments (QMA) of 84 rugby league players within a talent development environment. A one-way ANOVA showed Quartile 1 players were more mature, taller (173.0±7.4 vs 165.0±8.0 cm) and heavier (72.5 vs 58.7 kg) than Quartile 4 players, with no difference evident for fitness or QMA measures. Earlier maturing players had significantly greater upper body power (5.39±0.46 vs 4.42±0.68 m), 20m speed (3.48±0.14 vs 3.65±0.19s) and power pass QMA (13.88±2.18 vs 12.00±1.98) than later maturing players. Body mass was positively related to power pass fitness (r=0.50) and QMA (r=0.22) scores, with negative relationships found for vertical jump performance (r=−0.24), sprint QMA (r=−.29) and turn off either foot QMA (r=−0.26). There is a need to educate coaches about the use of both fitness testing and qualitative movement assessments to identify talented U14 rugby league players, which potentially reduces relative age and maturational biases.